2017
DOI: 10.1073/pnas.1711125114
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of individuals by trait prediction using whole-genome sequencing data

Abstract: Prediction of human physical traits and demographic information from genomic data challenges privacy and data deidentification in personalized medicine. To explore the current capabilities of phenotype-based genomic identification, we applied whole-genome sequencing, detailed phenotyping, and statistical modeling to predict biometric traits in a cohort of 1,061 participants of diverse ancestry. Individually, for a large fraction of the traits, their predictive accuracy beyond ancestry and demographic informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
119
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(136 citation statements)
references
References 49 publications
6
119
0
4
Order By: Relevance
“…Although cloud environments enable high‐capacity data storage (eg, Amazon Web Services, https://aws.amazon.com/), there are legitimate concerns about the privacy and security of sensitive cloud‐stored genetic data, indicating the need for more secure and decentralized solutions (eg, UnLynx) . Data sharing, which facilitates genotype‐phenotype correlation, is subject to further discussions as it has been shown that even after de‐identification, re‐identification of a single person is at least partially possible by either STR or SNP genotyping …”
Section: Regulatory Issues: Genetic Counseling Reimbursement and Datmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cloud environments enable high‐capacity data storage (eg, Amazon Web Services, https://aws.amazon.com/), there are legitimate concerns about the privacy and security of sensitive cloud‐stored genetic data, indicating the need for more secure and decentralized solutions (eg, UnLynx) . Data sharing, which facilitates genotype‐phenotype correlation, is subject to further discussions as it has been shown that even after de‐identification, re‐identification of a single person is at least partially possible by either STR or SNP genotyping …”
Section: Regulatory Issues: Genetic Counseling Reimbursement and Datmentioning
confidence: 99%
“…99 Data sharing, which facilitates genotype-phenotype correlation, is subject to further discussions as it has been shown that even after de-identification, re-identification of a single person is at least partially possible by either STR 100 or SNP genotyping. 101…”
Section: Variant Filtering and Interpretationmentioning
confidence: 99%
“…The ability to identify individuals based on portions of their DNA is possible [13]. Individuals can be identified through health records and physical samples provided to their health practitioners.…”
Section: Risks Of Human Harms Related To Privacymentioning
confidence: 99%
“…For smartphones, the algorithms must be scaled down, which makes them less effective, but in future with more sophistication of mobile phones it may become a handy tool for police officers/forensic scientists to recognize the accused/victim from a crowd [28]. A recent report has analyzed whole genomic sequencing data from different ethnic community around the world (#1061) which is able to identify people according to their physical traits and demography [29]. Morphometrics (the measurement of body shapes) may be used to identify the skeletal remains of missing children, something which is extremely challenging for current forensic experts.…”
Section: Facial Recognition Software and Morphometricsmentioning
confidence: 99%